Eating Attitudes of Students in High Schools in a Province Center, and Related Factors - Serdar Yıldırım; Ersin Uskun; Merve Kurnaz (Galenos Yayinevi, 2017)
Aim: Determining eating behaviours and negative eating behaviours especially during adolescent period, identifying the factors that can lead to negative eating attitudes can be directive in the prevention of obesity which is a public health problem, and associated diseases. The aim of this study was to assess the eating attitudes of students who were studying in high schools in a city center, and to examine the factors that may be associated with negative eating behaviors. Materials and Methods: In this cross-sectional, analytic type research 90.7% of the designated sample was reached (n=1263), data were collected by using a questionnaire about sociodemographic characteristics and eating attitudes test. Data were analysed using descriptive analysis, chi-square and logistic regression analysis in computer. Results with p-values less than 0.05 were considered statistically significant. Results: In univariate analysis, common school education, gender, health perception, body mass index (BMI) and family type were identified as the variables associated with the eating attitudes. In the multiple regression model, studying in a private school [odds ratio (OR)=2.9, p <0.001], female gender (OR=1.9, p=0.002), having a poor level of health perception (OR=4.9, p=0.029), and being overweight according to BMI (OR=1.9, p=0.039) were identified as risk factors for negative eating behaviors. Conclusion: Negative eating behavior is a condition which ruins the health perception of people and causes obesity, and these conditions can make eating behaviour worse in a vicious cycle. In this study, conditions which could be a risk factor for negative eating behaviors were evaluated, and female gender, studying in a private school, obesity, and having a negative health perception were especially defined as significant risk factors. Awareness activities should be done in risk groups in order to develop positive eating behaviors.